Longitudinal assessment of the inflammatory response: The next step in personalized medicine after severe trauma - de Fraiture, E. J.; Vrisekoop, N.; Leenen, L. P. H.; van Wessem, K. J. P.; Koenderman, L.; Hietbrink, F. (Frontiers in Medicine, 2022)
Infections in trauma patients are an increasing and substantial cause of morbidity, contributing to a mortality rate of 5-8% after trauma. With increased early survival rates, up to 30-50% of multitrauma patients develop an infectious complication. Trauma leads to a complex inflammatory cascade, in which neutrophils play a key role. Understanding the functions and characteristics of these cells is important for the understanding of their involvement in the development of infectious complications. Recently, analysis of neutrophil phenotype and function as complex biomarkers has become accessible for point-of-care decision making after trauma. There is an intriguing relation between the neutrophil functional phenotype on admission, and the clinical course (e.g., infectious complications) of trauma patients. Potential neutrophil based cellular diagnostics include subsets based on neutrophil receptor expression, responsiveness of neutrophils to formyl-peptides and FcRI (CD64) expression representing the infectious state of a patient. It is now possible to recognize patients at risk for infectious complications when presented at the trauma bay. These patients display increased numbers of neutrophil subsets, decreased responsiveness to fMLF and/or increased CD64 expression. The next step is to measure these biomarkers over time in trauma patients at risk for infectious complications, to guide decision making regarding timing and extent of surgery and administration of (preventive) antibiotics.